2007
DOI: 10.1016/j.juro.2007.01.116
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Prostate Volumes, Number of Biopsy Cores and 5α-Reductase Inhibitor Therapy on the Probability of Prostate Cancer Detection Using Mathematical Modeling

Abstract: Purpose: Previous studies demonstrated a negative correlation between prostate volume and biopsy yield. By decreasing prostate volume 5␣-reductase inhibitors may enhance cancer detection, which may explain the greater detection of high grade tumors in the finasteride arm of the Prostate Cancer Prevention Trial. Materials and Methods: A mathematical model was constructed to analyze the effects of prostate and tumor volumes, and biopsy core number on cancer detection. The effects of the volume reduction observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 21 publications
(28 reference statements)
3
16
0
Order By: Relevance
“…These data were similar to previous experiences from our centre and from other studies demonstrating a negative correlation between prostate volume and PCa diagnosis at biopsy. [12][13] Overall, PCa detection rate (40.4%) was the same as in other series in the extended biopsy protocol era. 14 Furthermore, our patients presented at least one metabolic abnormality among obesity, abnormal waist circumference and MS.…”
Section: Discussionsupporting
confidence: 74%
“…These data were similar to previous experiences from our centre and from other studies demonstrating a negative correlation between prostate volume and PCa diagnosis at biopsy. [12][13] Overall, PCa detection rate (40.4%) was the same as in other series in the extended biopsy protocol era. 14 Furthermore, our patients presented at least one metabolic abnormality among obesity, abnormal waist circumference and MS.…”
Section: Discussionsupporting
confidence: 74%
“…In other words, with decreasing prostate size, an increase in biopsy accuracy would occur given that cancer was present. Serfling et al (8), using a mathematical modeling system, suggested that given a baseline prostate size of 40 cm 3 and assuming a tumor volume of 1 cm 3 , a 25% decrease in prostate size would lead to an increase in tumor diagnosis of 21% using sextant biopsy. However, this study was unable to take into account low-grade versus high-grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This can increase the sensitivity of the biopsy and increase the likelihood of finding high-grade disease. Serfling et al 131 showed that a decrease of 25% in prostate volume (as occurs after finasteride treatment) can increase cancer detection by 23%.…”
Section: Risks Of Prostate Cancermentioning
confidence: 99%